Analysis of Human Resources Quality in Seaweed Production Development in Sumenep - Saidati Nor Wildana; Afifah, Zainiyatul; Kuswinarno, Mudji (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This research highlights the need for an integrated approach to enhance human resource quality for the sustainable development of seaweed production in Sumenep Regency. By focusing on Pagar Batu Village, Saronggi District, a significant seaweed-producing area, this study aims to support community welfare, particularly for coastal communities. Using a descriptive qualitative method with a case study approach, the research explores the dynamics of local seaweed cultivation, focusing on conditions as they naturally occur. Data collection involved observations, interviews, and documentation to capture a comprehensive view of seaweed production. Findings reveal both supporting factors, such as cooperative teamwork and adequate equipment, and obstacles like unpredictable weather, poor water quality, and fluctuating prices. Training programs organized by local authorities show potential in increasing technical knowledge, though outreach is still limited. This research underscores the importance of capacity building and technical training to address these challenges, fostering sustainable productivity and economic growth in Sumenep's seaweed sector.